The economic impact of immigration in Greece: taking stock of the existing evidence - Ioannis Cholezas; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2008)
Greece was traditionally an emigration country. However, since the early 1990s it became an immigrant destination and nowadays up to a tenth of the population are immigrants, mainly from neighbouring Balkan countries and, especially, Albania. This large scale immigration within a short time period had important social, as well as, economic consequences. The paper reviews the existing evidence and concludes that on average the economic effects of immigration were beneficial, although their distributional consequences were adverse. Greek immigration policy was haphazard and more efforts are needed in order to integrate the immigrants in the economic and social fabric of the country.
urn:nbn:de:101:1-2008112632
Keywords: F22; 330; Immigration; Greece; Einwanderung; Wirtschaftswachstum; Verteilungswirkung; Migrationspolitik; Soziale Integration; Griechenland